Chitosan-Based Biomaterial Scaffolds for the Repair of Infected Bone Defects - Tian, Yuhang; Wu, Danhua; Wu, Dankai; Cui, Yutao; Ren, Guangkai; Wang, Yanbing; Wang, Jincheng; Peng, Chuangang (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of infected bone defects includes infection control and repair of the bone defect. The development of biomaterials with anti-infection and osteogenic ability provides a promising strategy for the repair of infected bone defects. Owing to its antibacterial properties, chitosan (an emerging natural polymer) has been widely studied in bone tissue engineering. Moreover, it has been shown that chitosan promotes the adhesion and proliferation of osteoblast-related cells, and can serve as an ideal carrier for bone-promoting substances. In this review, the specific molecular mechanisms underlying the antibacterial effects of chitosan and its ability to promote bone repair are discussed. Furthermore, the properties of several kinds of functionalized chitosan are analyzed and compared with those of pure chitosan. The latest research on the combination of chitosan with different types of functionalized materials and biomolecules for the treatment of infected bone defects is also summarized. Finally, the current shortcomings of chitosan-based biomaterials for the treatment of infected bone defects and future research directions are discussed. This review provides a theoretical basis and advanced design strategies for the use of chitosan-based biomaterials in the treatment of infected defects